Blood urea nitrogen, blood urea nitrogen to creatinine ratio and incident stroke: The Dongfeng-Tongji cohort. (September 2021) - Peng, Rong; Liu, Kang; Li, Wending; Yuan, Yu; Niu, Rundong; Zhou, Lue; Xiao, Yang; Gao, Hui; Yang, Handong; Zhang, Chun; Zhang, Xiaomin; He, Meian; et al.
Abstract: Background and aims: It remains unclear whether extreme levels of blood urea nitrogen (BUN) and BUN to creatinine ratio (BUN/Cr) can increase future risk of stroke. We conducted this study to investigate the associations of BUN and BUN/Cr with incident stroke and its subtypes. Methods: A total of 26, 835 and 26, 379 participants with a mean follow-up of 7.9 years were included to investigate the associations of BUN and BUN/Cr with incident stroke, respectively. Cox proportional hazard models were used to evaluate hazard ratios (HRs) and 95% confidence intervals (CIs) for incident stroke and its subtypes. Results: Compared with participants in the third quintile of BUN, the adjusted HRs (95% CIs) for participants in the lowest quintile were 1.21 (1.04–1.40), 1.41 (1.18–1.68) and 1.36 (0.97–1.91) for total, ischemic and hemorrhagic stroke, respectively; while for those in the highest quintile, the corresponding HRs (95% CIs) were 1.16 (1.01–1.32), 1.30 (1.11–1.53), and 1.24 (0.90–1.71). The associations remained robust when restricting the analyses to participants within clinically normal range of BUN. For BUN/Cr, compared with participants in the third quintile, participants in the lowest quintile had significant higher risks of stroke (HRs [95% CIs] were 1.19 [1.04–1.37], 1.26 [1.07–1.48], and 1.22 [0.90–1.67] for total, ischemic and hemorrhagic stroke). Conclusions: Both high and low levels of BUN were associated with higher risks of total and ischemic stroke. Low level of BUN/Cr was associated with excess risks of total and ischemic stroke. Graphical abstract: Image 1 Highlights: Both lower and higher levels of BUN were associated with excess risks of total and ischemic stroke independent of eGFR. Extreme BUN levels, even within the clinically normal range, may confer potential risks of stroke previously unidentified. A U-shaped relationship was identified between BUN/Cr and total stroke and its subtypes.